Non-invasive Ventilation in Acute Respiratory Failure - Gurmeet Singh; Ceva W Pitoyo (Acta Medica Indonesiana)
One of the cornerstones of critical care medicine is support of the failing respiratory system. The 2 major components of managing respiratory failure are the acute intervention and the weaning process. Many of the studies to determine the optimal methods of ventilation and weaning have focused on non-invasive positive-pressure ventilation as an alternative to invasive ventilation, with various causes of acute respiratory failure. Non-invasive ventilation refers to the provision of ventilatory support to the lungs, without the use of an endotracheal airway. It has emerged as an important tool in the treatment of acute respiratory failure. Non-invasive positive ventilation has undergone a remarkable evolution over the past decades and is assuming an important role in the management of both acute and chronic respiratory failure. There is improvement in gas exchange, relief of respiratory muscle fatigue, and clinical outcome with reduced morbidity and mortality. Nevertheless, contraindications and failures need to be identified early, as delaying endotracheal intubation is associated with increased morbidity and mortality. Furthermore, although it is common practice to give intubation and mechanical ventilation, complications can result from the intubation process (damage to local tissue) and during the course of ventilation (pneumonia and sinusitis associated with ventilators), prolonging stay in intensive care, length of hospital stay and mortality in selected patients.